2019
DOI: 10.1212/wnl.0000000000007853
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol and risk of intracerebral hemorrhage

Abstract: ObjectiveTo prospectively examine the association between low-density lipoprotein (LDL) cholesterol (LDL-C) concentrations and intracerebral hemorrhage (ICH) risk.MethodsThe current cohort study included 96,043 participants (mean age 51.3 years) who were free of stroke, myocardial infarction, and cancer at baseline (2006). Serum LDL-C concentrations were assessed in 2006, 2008, 2010, and 2012. Cumulative average LDL-C concentrations were calculated from all available LDL-C data during that period. Incident ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 54 publications
(40 reference statements)
4
87
2
1
Order By: Relevance
“…The Asymptomatic Polyvascular Abnormalities in Community (APAC) study is a cross-sectional, community-based, and observational investigation designed to explore the epidemiology of asymptomatic polyvascular abnormalities in Chinese adults. The APAC study population was a part of the previously described Kailuan cohort [ 16 , 17 ], with 101,510 participants (18–98 years old). In 2010, 7000 participants aged over 40 were randomly selected from the Kailuan study by a random sampling method stratified by age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…The Asymptomatic Polyvascular Abnormalities in Community (APAC) study is a cross-sectional, community-based, and observational investigation designed to explore the epidemiology of asymptomatic polyvascular abnormalities in Chinese adults. The APAC study population was a part of the previously described Kailuan cohort [ 16 , 17 ], with 101,510 participants (18–98 years old). In 2010, 7000 participants aged over 40 were randomly selected from the Kailuan study by a random sampling method stratified by age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…Assessments of ICH incidence were conducted once a year during the follow-up period from 2006 to 2015, as detailed elsewhere. 16,17 Potential ICH incidence was ascertained from 4 complementary sources: (1) Municipal Social Insurance Institution, which covered all study participants; (2) Hospital Discharge Register centers; (3) death certificates; and (4) questionnaire survey (biennially since 2006). Potential cases of ICH included those who were identified by the ICD-10 based on the first 3 sources or those who self-reported as having ICH in the questionnaire survey.…”
Section: Assessment Of Incident Ichmentioning
confidence: 99%
“…Various forms of cell death have been identified after ICH, including apoptosis, necrosis, and autophagy in humans and experimental animals, and autophagic cell death in animal models [31][32][33]. Although inhibiting apoptosis, necrosis, and autophagy can improve outcomes in animals subjected to experimental ICH, no successful clinical trials using cell-death inhibitor monotherapy have been reported [34][35][36]. These facts suggest that multiple forms of cell death other than those mentioned above may occur after ICH and contribute collectively to neuronal death.…”
Section: Discussionmentioning
confidence: 99%